(untitled) (In situ, 2025)
Archaeological supervision and excavation were carried out during the construction of a residential building in Senj in the Alej area on cadastral plot 802/1 of the Senj land registry. On that occasion, the remains of a church-monastery complex with a cemetery were found, which was discovered and partially investigated in 2021. The site was not explored in its entirety, but only to the depth that would be devastated by construction works. The building whose remains were found during these excavations was demolished in the 16th century, when Ivan Lenković had all the buildings outside the walls of Senj demolished so that they would not serve as a fortress for the Turks in the immediate vicinity of the town. A cemetery was also found in the investigation, and five graves were explored. In the 18th or 19th century, a building with a square floor plan with two buttresses on the inside was built in this area, which functioned for a very short time. After that, the terrain was leveled, large amounts of soil were filled in, and the space acquired its current appearance.